2017
DOI: 10.1002/adfm.201701839
|View full text |Cite
|
Sign up to set email alerts
|

[4]Helicene–Squalene Fluorescent Nanoassemblies for Specific Targeting of Mitochondria in Live‐Cell Imaging

Abstract: Ester, amide, and directly linked composites of squalene and cationic diaza [4]helicenes 1 are readily prepared. These lipid‐dye constructs 2, 3, and 4 give in aqueous media monodispersed spherical nanoassemblies around 100–130 nm in diameter with excellent stability for several months. Racemic and enantiopure nanoassemblies of compound 2 are fully characterized, including by transmission electron microscope and cryogenic transmission electron microscope imaging that did not reveal higher order supramolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…In 2013, Lacour et al reported the synthesis of cationic [6]helicene as new members of chiral helicenium compounds. 269 Using a modular synthetic pathway, the authors were able to obtain heterohelicenes [278][BF 4 ]- [280][BF 4 ] on a multigram scale, the latter being resolved using (∆)-and (Λ)-BINPHAT anions in a similar way as for salt [260] [6]helicenium [280][BF 4 ] with electrophile and nucleophile reagents. Bottom: ECD and VCD spectra of (P)- [280][PF 6 ] (blue for ECD and red for VCD) and (M)- [280][PF 6 ] green for ECD and blue for VCD), with R = n-propyl.…”
Section: Synthesis Of Carbocationic Aza[6]helicenesmentioning
confidence: 99%
“…In 2013, Lacour et al reported the synthesis of cationic [6]helicene as new members of chiral helicenium compounds. 269 Using a modular synthetic pathway, the authors were able to obtain heterohelicenes [278][BF 4 ]- [280][BF 4 ] on a multigram scale, the latter being resolved using (∆)-and (Λ)-BINPHAT anions in a similar way as for salt [260] [6]helicenium [280][BF 4 ] with electrophile and nucleophile reagents. Bottom: ECD and VCD spectra of (P)- [280][PF 6 ] (blue for ECD and red for VCD) and (M)- [280][PF 6 ] green for ECD and blue for VCD), with R = n-propyl.…”
Section: Synthesis Of Carbocationic Aza[6]helicenesmentioning
confidence: 99%
“…Bacterial adhesion on these films was directly measured using scanning electron microscopy (SEM) upon dip-inoculation. Most importantly, we herein demonstrate the proof-of-concept that [7]helicene coated graphene monolayer (H-GR) have promising bacterial antifouling properties with a reduction in the bacterial adhesion of S. aureus up to 96.8% compared to bare graphene surfaces.…”
Section: Introductionmentioning
confidence: 78%
“…Helicene solution was prepared by dissolving 0.1% [7]helicene (purchased from Lach-Ner, Neratovice, Czech Republic, and used as received) in anhydrous dichloromethane via bath-sonication for 10 min at room temperature (23 • C). Then, 5 µL of helicene solution was spread at the air-water interfaces of a Langmuir trough (KSV Nima, Biolin Scientific, Gothenburg, Sweden) ( Figure 1).…”
Section: Methods and Experimentsmentioning
confidence: 99%
“…Compound 8 self‐assembled into Tyr‐MRI nanomicelles in aqueous media using either nanoprecipitation or thin‐film hydration method . The self‐assembly was surprisingly efficient.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoprecipitation method : 3.2 mg (1.0 μmol) of compound 8 was dissolved in a mixture of acetone (200 μL) and ethanol (200 μL). The organic phase was added dropwise into ultrapure water (1.40 mL) using a microsyringe in 5 min under magnetic stirring.…”
Section: Methodsmentioning
confidence: 99%